The elements of successful work placement processes: A case study of three Technical Vocational Education and Training (TVET) Colleges - Walters, Elizabeth (Graduate School of Development Policy and Practice, 2019)
Many research documents indicate that learners’ ability to transition from education and training to employment is closely linked to their work placement experience during their studies and on exit from their respective qualifications. This study identifies and analyses successful work placement practices through case studies, to understand which elements have supported TVET Colleges to facilitate the successful placement of their learners. The study starts with a historic overview of the Colleges to provide the context. It then moves on to explore, through secondary research, what the literature says about the identified elements which are institutional responsiveness; Work Integrated (WIL) units, curriculum relevance, partnerships and work readiness and their contribution to the transition from education to employment. The literature analysis was used to formulate key research questions for the primary research with three metro TVET Colleges, to explore how these Colleges have responded to the elements identified. The responses from the interviewees were used to extract the learnings from their practice and to draw out the elements that are key contributors to the successful placement of TVET learners.